UTHM Bicycle Rental Management System - Jamaluddin, Nazlia Afniza; Firkhan Ali Hamid Ali (Applied Information Technology And Computer Science, 2026)
The UTHM Bicycle Rental Management System is a web-based platform developed to address the inefficiencies in the current manual bicycle rental process at Universiti Tun Hussein Onn Malaysia (UTHM). This system aims to streamline rental operations and improve user satisfaction by providing features such as real-time bicycle availability and online reservations. Leveraging PHP for backend development, along with HTML, CSS, and JavaScript for the frontend, and MySQL for database management, the system offers a secure, scalable, and user-friendly interface. It utilizes the Agile methodology for iterative development, ensuring that user feedback is incorporated throughout the process. Key outcomes include reducing delays, minimizing manual workload, and enhancing operational efficiency. The system supports sustainable campus transportation and demonstrates the potential of digital solutions in transforming resource management. Future enhancements could expand its usability to broader contexts while integrating advanced analytics for better decision-making.